Genetic variation and reproduction strategy of Gentiana pannonica in different habitats - Ekrtová, Ester (Jihočeská univerzita, 2013)
The reproduction strategy and genetic variability of Gentiana pannonica, an endangered species in the Czech Republic, were studied. The differences of vegetation composition, seedlings recruitment, seed set and genetic variation within and among six various populations G. pannonica in the Šumava Mts. and two populations in the Alps of this species were investigated in a field. The vegetation composition differs between primary and secondary habitat of G. pannonica and seedlings recruitment was recorded only in primary habitat. The reproduction output of the study species is probably influenced by sufficient amount of pollinators. No serious genetic diversity between populations in the Šumava Mts. and the Alps was found. The genetic differences were found only between populations on the primary habitats and populations on the secondary mountain meadows.
Genetic variation and reproduction strategy of Gentiana pannonica in different habitats
Genetic variation and reproduction strategy of Gentiana pannonica in different habitats
Keywords: RAPD; refugia; secondary habitats; seedlings; the Bohemian Forest; the Alps; RAPD; refugia; secondary habitats; seedlings; the Bohemian Forest; the Alps